Applying theories of behaviour change to hearing health research: time for a new approach - Coulson, Neil S.; Ferguson, Melanie A.; Henshaw, Helen; Heffernan, Eithne (Taylor & Francis, 2016)
Objective: In recent years, there has been an increase in the application of behavioural models, such as social cognition models, to the promotion of hearing health. Despite this, there exists a well-developed body of literature that suggests such models may fail to consistently explain reliable amounts of variability in human behaviours. Design: This paper provides a summary of this research across selected models of health-related behaviour, outlining the current state of the evidence. Results: Recent work in the field of behaviour change is presented together with commentary on the design and reporting of behaviour change interventions. Conclusions: We propose that attempts to use unreliable models to explain and predict hearing health behaviours should now be replaced by work which integrates the latest in behaviour change science, such as the Behaviour Change Wheel and Theoretical Domains Framework.